P224 Harm associated with parenteral nutrition-related patient safety incidents reported to a national reporting system. (19th June 2022) - Mistry, Priya; Fox, Andy; Latter, Susan
Abstract : Introduction: Parenteral nutrition (PN)-related patient safety incidents (PSI) have been associated with harm, although large scale studies are scarce and little is known of contributory factors [1]. This study evaluated PN-related PSI that caused harm in England and Wales using the National Reporting and Learning System (NRLS). Method: A retrospective evaluation of PSI involving PN reported to the NRLS between April 2015 and March 2020, in all age groups. Quantitative analysis was used to describe frequency of PSI by degree of reported harm and other associated characteristics. Spearman's rho correlation was used to test the relationship between patient age and degree of harm. Qualitative content analysis was undertaken to understand contributory factors for PSI resulting in moderate/severe harm or death. Results: 12, 907 PSI were identified. All PSI causing moderate/severe harm, or death were provided (n=82), and a sample of PSI causing no/low harm (n=2248). After screening 2242 PSI were evaluated; 1879 (83.8%) resulted in no harm, 309 (13.8%) low harm, 47 (0.02%) moderate harm, 4 (0.002%) severe harm and 3 (0.001%) deaths. Neonates (<28 days) were the commonest age group (n=570/1923, 29.6%) across all PSI. The most reported medication process was administration (n=1126/2242, 50%), and most reported medication error category was omitted medication/ingredient (n=291/2242, 13%). There was an extremely weak positive correlation between the older patient age group and higher degree of harm (r=0.1, p<0.001). Content analysis revealed that age <1 year, dependence on home PN, co-morbidities and staff mistakes were common contributory factors in PSI causing moderate/severe harm or death. Conclusions: This is the first evaluation of PN-related PSI in England and Wales to our knowledge. We demonstrated a very low frequency of PSI causing moderate or severe harm or death. PN-related PSI in neonates were more frequently reported and most commonly occurred during the administration process. To reduce harm, systems and procedures that reduce errors in high-risk patients e.g., neonates and those dependent on home PN need to be established within organisations. Further evaluation of the no harm group is needed to understand 'near misses'. Database limitations of voluntary reporting systems were recognised. Reference: Mistry P, Smith RH, Fox A. Patient Safety Incidents Related to the Use of Parenteral Nutrition in All Patient Groups: A Systematic Scoping Review. Drug Saf . 2021. doi:10.1007/s40264-021-01134-3.